Stress resets ebook How to soothe your body and mind in minutes. - Taitz, Jennifer L. (2024)
A clinical psychologist gives us 75 quick, scientifically proven techniques and exercises to manage stress and build resilience.   Here’s a promise that could not be more timely or needed: You can dial down your stress in just a few minutes, with no ponderous meditations, medications, or martinis required. Written by Dr. Jennifer L. Taitz, a clinical psychologist who specializes in teaching mindfulness-based behavioral skills to manage intense emotions and situations, Stress Resets    provides 75 scientifically proven ways to improve how you respond to stress, both in the moment and the long run. There are accessible yet powerful exercises like dipping your face in ice water to quiet your body and mind; adopting a half smile to change your mood from the outside in; singing your irrational negative thoughts to reduce their believability; building a hope kit so you can remind yourself of what’s possible in tough moments; and making a pie chart of your life to gain perspective. By incorporating these into your days, you can stop the cycle of obsessing, panicking, and avoiding and instead effectively approach what matters to you most. You’ll also find stress buffers designed to build your resilience so you can navigate whatever comes your way. Through personal anecdotes, expert interviews, cutting-edge studies, and practical tips, you’ll learn how to manage your emotions instead of the other way around. Stress Resets will not only change how you view your stress but also give you the hope and confidence you need to reset and ultimately change how you feel.